Clinical trials of nanoparticle-enhanced CAR-T and NK cell therapies in oncology: overcoming translational and clinical challenges - a mini review - Zhao, Xiaoqian; Xiong, Jian; Li, Danyang; Zhang, Ying (Frontiers in Medicine, 2025)
Chimeric antigen receptor (CAR) T-cell and natural killer (NK) cell therapeutic approaches have significantly reshaped the immuno-oncology domain for hematological malignancies. These approaches have sustained therapeutic results in patients with treatment-resistant disease and exhibited robust therapeutic efficacy. However, poor immune cell trafficking, tumor-induced immune suppression, and complex ex vivo modification limit their clinical application in solid tumors. The application of nanotechnology has transformed efforts to overcome these limitations by promoting in vivo expression of CARs, enabling tumor-selective immunomodulation, and allowing site-specific dynamic cytokine modulation. This mini review provides critical valuations of the current clinical trials, focusing on the regulatory challenges, design rationale, and translational advances. This article highlights ongoing challenges, recent developments, and future directions for the clinical translation of advanced immunotherapeutic strategies.